2018
DOI: 10.1016/j.epsl.2018.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate stability in the reduced lower mantle

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 71 publications
5
47
0
Order By: Relevance
“…The residual carbide phases observed in DAC experiments were fully converted into elemental carbon at 20 GPa with longer heating time at high temperature. Our DAC and MA experiments confirm the two-step reaction between magnesite and iron metal, which first forms carbide and then diamond, as found in previous studies (Dorfman et al, 2018;Palyanov et al, 2013;Rohrbach & Schmidt, 2011). C+(Mg,Fe)O is therefore more stable than Fe 3 C/Fe 7 C 3 + MgCO 3 over the entire mantle pressure range.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The residual carbide phases observed in DAC experiments were fully converted into elemental carbon at 20 GPa with longer heating time at high temperature. Our DAC and MA experiments confirm the two-step reaction between magnesite and iron metal, which first forms carbide and then diamond, as found in previous studies (Dorfman et al, 2018;Palyanov et al, 2013;Rohrbach & Schmidt, 2011). C+(Mg,Fe)O is therefore more stable than Fe 3 C/Fe 7 C 3 + MgCO 3 over the entire mantle pressure range.…”
Section: Resultssupporting
confidence: 90%
“…The residual carbide phases observed in DAC experiments were fully converted into elemental carbon at 20 GPa with longer heating time at high temperature. Previous studies also suggested production of elemental carbon in a similar reaction at 51-113 GPa (Dorfman et al, 2018). C+(Mg,Fe)O is therefore more stable than Fe 3 C/Fe 7 C 3 + MgCO 3 over the entire mantle pressure range.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, octahedral diamonds in peridotitic and eclogitic rocks displayed a spiral growth mechanism, indicating that the crystal moved freely in carbon-bearing silicate melt (Bulanova, 1995). The formation and growth of diamonds has been experimentally observed in a kim berlitic melt at 1800 °C-2200 °C and 7-7.7 GPa (Arima et al, 1993), and from dolomite+iron through carboniron redox reactions (Dorfman et al, 2018). However, the coordination of carbon in the melt and the mechanism of subsequent polymerization of carbon could not be deter mined due to limitations in experimental techniques.…”
Section: Diamond Formationmentioning
confidence: 99%
“…What is more, recent theoretical studies indicate that direct decomposition of CaCO 3 and MgCO 3 is unfavorable over the lower mantle, putting into doubt the possibility of free CO 2 existing at these depths (Pickard & Needs, 2015;Santos et al, 2019). It should be also emphasized that possible chemical processes, involving either reactions of CO 2 or carbonates with elemental iron of the Earth's outer core close to the core-mantle boundary (Dorfman et al, 2018;Martirosyan et al, 2019), or with hydrous iron minerals like goethite (Boulard et al, 2018), can dramatically change carbon speciation in the lower mantle. In light of these findings, drawing conclusions concerning the deep carbon cycle on the basis of high pressure-high temperature behavior of pure CO 2 requires extreme care.…”
Section: Carbon Dioxide Stability Versus Dissociationmentioning
confidence: 99%